The Effect of Work Ethic, Tenure, and Facilities on Employee Productivity at PKU Muhammadiyah Aghisna Kroya General Hospital - Firdaus, Arsya; Andriani, Rian; Widjaja, Yani Restiani (Journal of Economics and Social Sciences (JESS), 2025)
This study aims to analyze the influence of work ethic, length of service, and facilities on employee productivity at RSU PKU Muhammadiyah Aghisna Kroya, both partially and simultaneously. The approach used is quantitative with a descriptive survey method. Data were obtained through questionnaires distributed to 167 respondents selected using simple random sampling techniques. Data analysis was carried out using statistical tests, including univariate analysis, bivariate with Pearson and Chi-Square correlation tests, and multivariate analysis with multiple linear regression to evaluate the simultaneous influence of independent variables on employee productivity. The results showed that work ethic has a positive and significant effect on employee productivity. Length of service has an effect on productivity, although the level of influence is lower than work ethic. Work facilities have a significant effect on productivity, indicating that the availability of adequate facilities can increase work effectiveness. Simultaneous analysis shows that work ethic, length of service, and facilities together affect employee productivity, with a coefficient of determination (R²) value indicating that these three variables are able to explain most of the variation in productivity. Efforts to increase productivity can be made by strengthening work ethic, optimizing length of service, and providing better facilities for employees.